Regulation of the glyoxylate bypass operon: cloning and characterization of iclR - A Sunnarborg; David J. Klumpp; T Chung; D C LaPorte (1990)
In Escherichia coli, expression of the glyoxylate bypass operon appears to be controlled, in part, by the product of iclR+. Mutations in iclR have been found to yield constitutive expression of this operon, suggesting that iclR+ encodes a repressor protein. We have cloned iclR+ by taking advantage of its tight genetic linkage with the glyoxylate bypass operon. The clone complemented a mutant allele of iclR in trans, restoring an inducible phenotype for this operon. Deletion analysis identified a region of ca. 900 base pairs that was necessary and sufficient for complementation. The nucleotide sequence of the insert was then determined. Translation of this sequence revealed an open reading frame capable of encoding a protein with Mr 29,741 preceded by a potential Shine-Dalgarno ribosome-binding site. The deduced amino acid sequence includes a region at the amino terminus that may form a helix-turn-helix motif, a structure found in many DNA-binding domains.